177k views
2 votes
Translate the sentence into an equation using n to represent the unknown number. Then solve the equation for n.

a number subtracted from 46 is -21
a.
46 minus n = negative 21. n = 67
b.
46 minus 21 = n. n = 67
c.
46 minus 21 = n. n = 25
d.
46 minus n = negative 21. n = 75

User Pruivo
by
6.5k points

1 Answer

7 votes

Answer: a.

Explanation:

46 is subtracted by n to get -21 so the equation is 46 - n = -21

Add n on both sides; 46 - n + n = -21 + n; 46 = -21 + n

Add 21 on both sides; 46 + 21 = -21 + n + 21; 67 = n

So n = 67

User Mudit Saklani
by
6.0k points